Selinexor, a selective inhibitor of nuclear export, inhibits human neutrophil extracellular trap formation in vitro - Baron, Szilvia; Rashal, Tami; Vaisman, Dmitry; Elhasid, Ronit; Shukrun, Rachel (Frontiers in Pharmacology, 2022)
Neutrophils are central players in the innate immune system. To protect against invading pathogens, neutrophils can externalize chromatin to create neutrophil extracellular traps (NETs). While NETs are critical to host defense, they also have deleterious effects, and dysregulation of NETs formation has been implicated in autoimmune diseases, atherosclerosis and thrombotic conditions, cancer progression and dissemination, and acute respiratory distress syndrome. Here, we report that selinexor, a first-in-class selective inhibitor of nuclear export approved for the treatment of multiple myeloma and diffuse large B-cell lymphoma, markedly suppressed the release of NETs in vitro. Furthermore, we demonstrate a significant inhibitory effect of selinexor on NETs formation, but not on oxidative burst or enzymatic activities central to NETs release such as neutrophil elastase, myeloperoxidase or peptidyl arginine deiminase type IV. The inhibitory effect of selinexor was demonstrated in neutrophils activated by a variety of NETs-inducers, including PMA, TGF-β, TNF-α and IL-8. Maximal inhibition of NETs formation was observed using TGF-β, for which selinexor inhibited NETs release by 61.6 %. These findings pave the way to the potential use of selinexor in an effort to reduce disease burden by inhibition of NETs.